Industry 4.0 Perspectives and Applications - Gordan, Meisam; Ghaedi, Khaled; Saleh, Vala (Artificial Intelligence, 2023)
This book presents an overview of Industry 4.0 (IR4.0) technologies including the Internet of Things (IoT), big data, data mining, deep learning, machine learning, Artificial Intelligence (AI), and cloud/edge computing. It also provides detailed insight into the impact of cutting-edge technologies such as the Internet of Services (IoS), innovative sensing strategies, and cyber-physical systems on IR4.0 as well as data-driven, real-time detection, and condition monitoring applications.